(untitled) (Web of Teachers: Inderscience Research, 2026)
Emotional deprivation, as a phenomenon, plays a critical role in shaping the intricate dimensions of social alienation and loneliness, significantly impacting modern societies. At its core, emotional deprivation is characterized by the persistent absence or inadequacy of emotional support, affection, or validation, experienced in individuals’ formative environments or throughout significant interpersonal relationships. This lack of emotional nurturing does not merely remain a transient emotional state; rather, it transforms into a profound psychosocial factor that fundamentally influences one’s perceptions of self, relationships with others, and even the broader structure of social life.